2020
DOI: 10.5194/acp-2020-463
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increasing manmade air pollution likely to reduce rainfall in southern West Africa

Abstract: Abstract. Southern West Africa has one of the fastest growing populations worldwide. This has led to a higher water demand and lower air quality. Over the last three decades, most of the region has experienced decreasing rainfall during the little dry season (LDS, mid-July to end of August) and more recently also during the second rainy season (SRS, September–October), while trends during the first rainy season (FRS, mid-May to mid-July) are insignificant. Here we use spatio-temporal variations of precipitatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
2
0
0
Order By: Relevance
“…Furthermore, the reduction of precipitation in southern West Africa due to the anthropogenic aerosol emitted along the coast, changes the liquid water transported towards the Sahel, and modifies the winds and soil humidity, and as a consequence dust emissions, as shown by Menut et al (2019). The present study adds evidence to the emerging hypothesis that, during the West African monsoon, increasing anthropogenic aerosol pollution in southern West Africa has already caused a precipitation reduction (Pante et al, 2020).…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, the reduction of precipitation in southern West Africa due to the anthropogenic aerosol emitted along the coast, changes the liquid water transported towards the Sahel, and modifies the winds and soil humidity, and as a consequence dust emissions, as shown by Menut et al (2019). The present study adds evidence to the emerging hypothesis that, during the West African monsoon, increasing anthropogenic aerosol pollution in southern West Africa has already caused a precipitation reduction (Pante et al, 2020).…”
Section: Discussionsupporting
confidence: 64%
“…A few studies have nevertheless suggested continental-scale connections between the central and southern Africa biomass-burning (SABB) aerosol radiative forcing and tropical Africa precipitation, mostly attributed to the perturbation of continental static stability 7 . Recent studies have also pointed out that a fraction of SABB particles, once northwardly advected over West Africa, could contribute to impacting the local climate via cloud interactions 8 or modification of local atmospheric stability 9,10 , Here, we show that SABB can also have an important effect on WAM through a regional inter-hemispheric dynamical feedback originating from the highly concentrated SABB aerosol outflow located over the South Eastern Atlantic (SEA) ocean (Fig. 1, region A).…”
Section: Introductionsupporting
confidence: 59%